Lactate-induced lactylation: from basic research to clinical perspectives - Shi, Henghe; Zou, Yifei; Jin, Sijie; Wu, Junduo; Liu, Bin (Frontiers in Pharmacology, 2025)
Lactate was initially considered a metabolic waste product of glycolysis under hypoxic conditions until the emergence of the lactate shuttle hypothesis. The lactate shuttle hypothesis describes the role of lactate in the delivery of oxidative and gluconeogenic substrates as well as in cell signaling. Lactate is a key molecule that links cellular metabolism to the regulation of cellular activity. Lactate-induced lactylation was first identified and reported in Nature in 2019 by Zhang et al. Subsequently, many studies on lactylation have been reported. Widely distributed lactylation is involved in a myriad of pathological processes and participates in the development and progression of numerous diseases, offering promising potential for future disease treatments. We comprehensively reviewed and organized the existing literature, detailed the metabolic processes of lactate and lactylation, and summarized the existing research methods on lactylation, aiming to provide direction and convenience for future research in this field. Additionally, we summarized the role of lactylation in various pathophysiological processes and elucidated the relationship between lactate modification and various diseases, as well as the targets and drugs that regulate lactylation, which may enable future clinical interventions.